Ganoderma lucidum protease hydrolyzate on lipid metabolism and gut microbiota in high-fat diet fed rats. (June 2022) - Xiong, Yu; Zhang, Feng-Li; Li, Jing-Ru; Peng, Pei-Zhi; Liu, Bin; Zhao, Li-Na
Abstract: In this study, we aimed to evaluate the effect of Ganoderma lucidum protease hydrolysate (GLPH) on lipid metabolism and intestinal flora in rats fed on a high-fat diet. Our research shows that GLPH reduces triglycerides, total cholesterol, low-density lipoprotein cholesterol, alanine aminotransferase and aspartate aminotransferase levels, but increases high-density lipoprotein cholesterol in the serum and liver. Besides, GLPH has hypolipidemic effects, such as sterol regulatory element-binding transcription factor 1C, acetyl-coenzyme A carboxylase at the liver mRNA level were down-regulated, 5′-adenosine monophosphate (AMP)-activated protein kinase, acyl-CoA oxidase, farnesoid X receptor and peroxisome proliferator-activated receptor α at the liver mRNA level was upregulated. GLPH treatment changes the composition of the intestinal flora and reduces the relative abundance of potentially harmful bacteria, such as Alistipes, Clostridium . Spearman's correlation analysis showed that changes in faecal microbiota are related to biochemical indicators. In summary, our research indicates that GLPH can improve lipid metabolism disorders, regulate the structure of intestinal microbes, and can be used as a lipid-lowering functional food.